MODEL SISTEM PERENCANAAN PRODUKSI TERINTEGRASI DI INDUSTRI PERCETAKAN - Antono Adhi (Jurnal Ilmiah Dinamika Teknik, 2014)
Production planning is an important activity in production proess. Production processes will be done effectively and efficiently by a good planning, because gap of production caused by constraint and limitation will be conducted back to the first goal of production process. Monitoring and evaluation process are needed in this actvity. Production process in printing industry is also need this activity. Main activities in production panning are production scheduling and material requirement planning (MRP) based on both production ordering or forecasting. This activities of planning is very complex therefore the system must developed based on computer using optimum methods to solve, namely heuristic method. Key words: production planning, production scheduling, MRP, heuristic method